Anthropogenic noise and biological sounds in a heavily industrialized coastal area (Gulf of Naples, Mediterranean Sea). (July 2020) - Pieretti, N.; Lo Martire, M.; Corinaldesi, C.; Musco, L.; Dell'Anno, A.; Danovaro, R.
Abstract: Underwater noise is one of the most widespread threats to the world oceans. Its negative impact on fauna is nowadays well established, but baseline data to be used in management and monitoring programs are still largely lacking. In particular, the acoustic assessment of human-impacted marine coastal areas provides complementary information on the health status of marine ecosystems. The objective of our study was to provide a baseline of underwater noise levels and biological sounds at two sites within the Gulf of Naples (Italy), one of which is located in Bagnoli-Coroglio, a Site of National Interest (SIN) for its high contamination levels. Within the SIN, sounds were recorded both before and during sediment coring activities (vibrocorer sampling), in order to investigate the potential acoustic impact due to such operations. Acoustic recordings were analyzed following the European Marine Strategy Framework Directive indications as defined in the frame of the Descriptor 11. Results reported here show that the investigated area is characterized by a high anthropogenic noise pressure. Ambient noise levels were principally driven by shipping noise and biological sounds of invertebrates (e.g., snapping shrimps). Sounds referable to other biological activity were difficult to detect because heavily masked by shipping noise. Coring activity determined a substantial introduction of additional noise at a local spatial scale. This study expands underwater noise baseline data to be further implemented in future monitoring programs of coastal areas affected by anthropogenic impacts. In addition, it proposes new cues for using underwater acoustic monitoring tools to complement traditional methodologies for evaluating health status of ecosystems and for investigating recovery rates after restoration/reclamation programs. Highlights: Acoustic baseline data for management and monitoring programs are urgently required. Ambient noise levels and biological sounds in the Gulf of Naples (Italy) were shown. Results showed the presence of a high noise pressure in the investigated area. Biological sounds were less diverse at the SIN of Bagnoli-Coroglio.